Hunter-gatherers, biogeographic barriers and the development of human settlement in Tierra del Fuego - Morello, Flavia (2012)
Tierra del Fuego represents the southernmost limit of human settlement in the Americas. While people may have started to arrive there around 10 500 BP, when it was still connected to the mainland, the main wave of occupation occurred 5000 years later, by which time it had become an island. The co-existence in the area of maritime hunter-gatherers (in canoes) with previous terrestrial occupants pre-echoes the culturally distinctive groups encountered by the first European visitors in the sixteenth century. The study also provides a striking example of interaction across challenging natural barriers.